Pengenalan Terapi Musik Mozart dan Murrotal Al-Qur’an sebagai Upaya Nonfarmakologis untuk Mengurangi Nyeri Persalinan pada Ibu Bersalin di Klinik H. Syahruddin Tanjung Balai - Andika, Rindy Arabella Margareta; Wulandary, Herviza; Joharmi (Cattleya Darmaya Fortuna, 2025)
Health education with a spiritual approach is a strategic effort to provide holistic support to pregnant women, especially in the lead-up to childbirth. This education activity aims to increase pregnant women's understanding of the importance of mental and spiritual preparedness through the use of Qur'anic mosaics, which are fragments of Qur'anic verses relevant to the birthing process. The education material includes verses containing messages of calm, strength, and trust, such as Surah Maryam, Surah Al-Insyirah, and Surah Al-Baqarah. The methods used include lectures, interactive discussions, and relaxation simulations with the recitation of Qur'anic verses. The results of the activity showed an increase in participants' understanding of the importance of a spiritual approach in facing childbirth, as well as the emergence of a sense of calm and confidence. This education is expected to become part of maternal health promotion based on Islamic values and become a routine program in health care facilities. Labor pain is one of the most intense forms of physiological pain experienced by women and often causes tension and anxiety in mothers during labor. Pain management can be achieved using non-pharmacological methods such as classical music therapy and Quranic recitation. This counseling program aims to compare the effectiveness of Mozart's classical music therapy and Quranic recitation in reducing labor pain intensity during the active phase of labor at the Syahruddin Clinic in 2025. This counseling uses a method. A total of 30 respondents were sampled, divided into two groups of 15 respondents each, namely the Mozart classical music therapy group and the Al-Qur'an music group. The results showed a significant decrease in pain intensity after the therapy given to each group. This counseling is that Al-Qur'an imurotal therapy is proven to be more effective in reducing labor pain in the active phase of stage 1, so this therapy can be considered as an alternative to pharmacological intervention in obstetric services.